2015
DOI: 10.1016/j.urolonc.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia is an independent predictor of inferior outcome in papillary renal cell carcinoma

Abstract: Purpose Lymphopenia as a likely index of poor systemic immunity is an independent predictor of inferior outcome in clear renal cell carcinoma (ccRCC). We sought to evaluate the prognostic relevance of preoperative absolute lymphocyte count (ALC) in a cohort of papillary renal cell carcinoma (PRCC) patients. Materials & Methods A prospectively maintained, renal cancer database was analyzed. Patients with preoperative ALC, within 3 months prior to surgery, were eligible for the study. Those with multifocal or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 28 publications
3
29
0
Order By: Relevance
“…Our study showed that lymphopenia was associated with N stage. This observation is in line with data from Saroha et al, 13 but is contrary to the result of Mehrazin et al, 19 who suggested that lymphopenia is not correlation with the N stage ( P = 0.120).…”
Section: Discussionsupporting
confidence: 85%
“…Our study showed that lymphopenia was associated with N stage. This observation is in line with data from Saroha et al, 13 but is contrary to the result of Mehrazin et al, 19 who suggested that lymphopenia is not correlation with the N stage ( P = 0.120).…”
Section: Discussionsupporting
confidence: 85%
“…Lymphocytes play an important role in cell-mediated immune response activation and tumor cell demolition. [ 35 , 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…de Martino et al [ 13 ] showed that patients with increased preoperative NLR, evaluated as a continuous variable, had a high risk of disease recurrence in nonclear cell RCC. Mehrazin et al [ 14 ] demonstrated that patients with lymphopenia had an inferior overall survival and a trend significance for worse cancer-specific survival ( P = 0.071) in pRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study investigated NLR in nonclear cell RCC, but they did not analyze it in separate histologic subtype [ 13 ]. One recent study focused on ALC in pRCC [ 14 ].…”
Section: Introductionmentioning
confidence: 99%